Challenges and inequalities in the management of financing the tasks of local government units: a critical analysis - Ciach, Arkadiusz (Nowoczesne systemy zarządzania, 2024)
Research objectives and hypothesis/research questions The aim is to critically analyze the challenges and inequalities in the management of the financing of the tasks of local government units (LGUs) in Poland, with particular emphasis on the impact of legislative, political, and financial factors on the effectiveness of their tasks. Research questions: 1. Does the presence of councilors employed in units subordinate to local government units lead to a conflict of interest, which negatively impacts the transparency and independence of financial decisions made? 2. Does the amount of subsidies and subsidies awarded depend solely on the economic situation of municipalities, or is it also influenced by political links between local authorities and the ruling party at the central level? 3. As a result of underestimating the educational subsidy, are local government units forced to redirect their funds to finance educational tasks at the expense of other public activity areas? 4. Do the currently used algorithms for the distribution of subsidies reflect the real needs of local government units, and, as a result, there is an optimal allocation of public funds? 5. Is there equal access for local government units to European and national funds? Research methods 1. Analysis of empirical data: Examination of data from local government units (LGUs) between 2019 and 2023. 2. Comparative analysis: Evaluation of financial indicators for LGUs based on their size, own revenues, and political affiliations. 3. Statistical analysis: Investigation of differences in the allocation of financial resources to identify disparities. 4. Analysis of source documents: Review legal documents, Supreme Audit Office (NIK) reports, and local budget data from LGUs. 5. Case study: Analysis of municipalities in the Radomsko focusing on underestimating educational subsidies and conflicts of interest. 6. Critical literature review: Examination of domestic and international literature to provide context and identify relevant issues. Main results 1. The amount of subsidies and grants awarded often depends on the political affiliations of local authorities with the ruling party. 2. Educational subsidies fall short of covering actual educational costs, straining resources for other public responsibilities. 3. Councilors employed by subordinate LGU units cause conflicts of interest, harming transparency and financial independence. 4. Under governmental support programs, grant allocation processes lacked transparency and clear criteria, enabling abuses and discretionary fund distribution. 5. Financial support was unevenly distributed, worsening inequalities between wealthier and poorer regions. Implications for theory and practice For theory: the research brought a new perspective to the analysis of decentralization and self-government, showing the impact of political, legislative, and financial factors on the functioning of local governments. In particular, the results confirm the importance of political distribution theory, pointing to the practice of favoring individuals associated with the ruling party, reflecting the phenomenon of political allocation of resources. The problems of unequal allocation of resources and underestimation of education subsidies bring new elements to the theory of distributive justice, highlighting the imbalance in access to public resources between regions. For practice: research indicates an urgent need for legislative reforms aimed at simplifying and stabilizing the regulations governing the activities of local government units. Recommendation for the introduction of more transparent mechanisms for allocating public funds. Emphasize the importance of support for less developed local government units, which would reduce regional inequalities and make more efficient use of available funds.